Incidence Rate and Clinical Characteristics of Triple Negative Breast Cancer Patients in Hasan Sadikin Hospital, for the Last Five Years - Dodi Lintong Hartoni Lumban Gaol; Kiki Akhmad Rizki; Monty Priosodewo Soemitro (International Journal Labs, 2023)
Breast cancer is the most common cancer in Indonesia and ranks as the first cause of cancer death. Data from the Global Cancer Observatory (GLOBOCAN) 2020 shows that as many as 16.6% of the total 396,914 new cases of cancer in Indonesia are breast cancer with a mortality rate of more than 22 million. This study took all data on breast cancer patients at Hasan Sadikin Hospital (RSHS) from 2015-2019. Where from all this data, then the inclusion criteria are patients who have TNBC from immunohistochemistry analysis. From all existing samples, the patient's age is then recorded and then grouped. This age mapping is to find out what age group TNBC occurs the most. Of the 4050 breast cancer patients who went to RSHS in 2015-2019, 628 patients showed supportive immunohistochemistry results towards a triple negative diagnosis. From all these data, it was then found that the age group that was most diagnosed with TNBC in RSHS was 41-50 years old, which was 237 people or about 37%. From all existing data, a recidivist incidence rate of 11 cases or around 1.7% was obtained. TNBC is a malignant and aggressive type of breast cancer because the immunohistochemistry (IHC) presentation does not have three receptors that can be found in other types of breast cancer, namely estrogen (ER), progesterone (PR), and a protein known as human epidermal growth factor (HER2). This research has limitations, namely that the data available is very minimal so that it is considered less representative. Research on a larger scale and longer time is needed to provide a more real and representative picture.